Clinical Efficacy and Safety of the EX-PRESS Filtration Device in Patients with Advanced Neovascular Glaucoma and Proliferative Diabetic Retinopathy - Rana Hanna; Beatrice Tiosano; Shmuel Graffi; Dan Gaton (Case Reports in Ophthalmology, 2018)
Background: The prognosis of conventional filtration surgery in eyes with neovascular glaucoma (NVG) is limited due to increased fibrovascular proliferation or bleeding. This study aims to evaluate the safety and efficacy of the EX-PRESS filtration device in the management of NVG associated with proliferative diabetic retinopathy (PDR). Methods: In this retrospective case series, we reviewed the medical records of patients diagnosed as having NVG associated with PDR who underwent EX-PRESS filtration surgery. The main outcome measures were: postoperative intraocular pressure (IOP), the percent of IOP drop, the number of glaucoma medications, visual acuity, and complications of surgery. Successful surgery was defined as an IOP <22 mm Hg and >5 mm Hg with or without additional glaucoma surgery, and no loss of light perception or less than a 2-line decrease on the Snellen chart of the best corrected visual acuity (BCVA). Results: Five patients (5 eyes) were included in this study. The mean preoperative IOP was 33.4 ± 5.9 mm Hg compared to an IOP of 17.0 ± 3.0 mm Hg at the last follow-up (p = 0.003). The mean number of preoperative anti-glaucoma medications was 3.8 ± 0.4 compared to 2.2 ± 1.5 (p = 0.06) at the last follow-up visit. Final visual acuity improved or stabilized within 1 Snellen line in all 5 patients. Three patients had a “hypertensive phase” (defined as an IOP >21 mm Hg during the first 6 postoperative months) which resolved within 2 months. Two patients developed a hyphema that resolved spontaneously. None of the patients experienced any serious complications. Conclusion: EX-PRESS filtration device has a good IOP-lowering effect and a low rate of complications in patients with advanced NVG associated with PDR. In addition, there was no loss of light perception or no line decrease of the BCVA.